Closing the Gender Gap in Agriculture. (1st January 2016) - Huyer, Sophia
Abstract: Agriculture is the largest employment sector for 60% of women in Oceania, Southern Asia and sub-Saharan Africa and women make up 2/3 of the world's 600 million small livestock managers. Despite this, women's activities in agriculture are characterised by a global gender gap in vulnerabilities, access to resources, and productivity. As a result of these differences, women and men farmers in developing countries have different abilities to adapt to climate change. But addressing gender inequalities in agriculture to address climate change involves more than erasing inequities in access to resources. The question of whether women have control of these resources; whether they participate in use of and decisions around the accrued benefits of increased production and income, and whether resources meet their requirements and priorities, will all determine whether the gender gap in agriculture is closed. It also involves ensuring that women's needs and priorities are met, in terms of how priorities are set, modes of support and resources. Technologies to support resilience and adaptation to climate change by smallholder farmers can promote women's empowerment and the transformation of gender relations in addition to sustainably increasing agricultural production. But this will only happen if they are implemented in a framework of mutually reinforcing resources, women's control of assets, equitable decisionmaking between women and men, and strengthened capacity.